Impacts of natural and anthropogenic factors on soil erosion - Nomin Gantulga; Tuyajargal Iimaa; Munkhjin Batmunkh; Unursaikhan Surenjav; Enkhjargal Tserennadmin; Telmen Turmunkh; Dorjgotov Denchingungaa; Batsuren Dorjsuren (Proceedings of the Mongolian Academy of Sciences)
Soil erosion is a serious issue that is caused by both natural and anthropogenic factors. Natural processes, including water and wind erosion, as well as higher temperatures, have been identified as leading causes of soil erosion. Additionally, anthropogenic factors, such as urbanization, road construction, agriculture, industry, mining, and others significantly contribute to this problem. These factors have resulted in the loss of biological productivity of the land and have inflicted damage on the entire ecosystem. Since 2000, soil erosion and desertification have become even more severe, exacerbating the problem. The soil of Mongolia, characterized by an arid and semi-arid climate with low precipitation and high temperature fluctuations, is highly susceptible to erosion with approximately 55% of it being classified as high or very easy to erode. This review provides a comprehensive overview of the natural processes and anthropogenic factors that contribute to soil erosion, as well as the current status of soil in various regions of Mongolia.